Hypertension and Cardiac Organ Damage - Izzo, Raffaele (Springer International Publishing : Imprint: Springer, 2017)
This book identifies the key determinants in the management of hypertensive outpatients with Cardiac Target Organ Damage. It sheds light on current international guidelines by directly applying them to six representative clinical cases that reflect situations frequently encountered during clinical routine rather than emergencies or rare occurrences. The book enables cardiologists and angiologists alike to gain an overview of the most frequent cardiac dysfunctions related to hypertension: left atrial enlargement, aortic root dilatation, diastolic dysfunction, systolic dysfunction, left and right ventricular enlargement. Each case is illustrated and analyzed in detail - from family and personal history to treatment and follow-up - providing readers with valuable guidance that will help them to select the best suited diagnostic tool and treatment for each patient.
Keywords: Medicine.; Angiology.; Cardiology.; Nursing.; elektronické knihy; electronic books